2021
DOI: 10.1111/jcmm.16923
|View full text |Cite
|
Sign up to set email alerts
|

Oridonin prevents oxidative stress‐induced endothelial injury via promoting Nrf‐2 pathway in ischaemic stroke

Abstract: Stroke is the second leading cause of global mortality and the major cause of neurological disability. 1 At present, thrombolysis and thrombectomy are the main treatments for ischaemic stroke. 2 However, current effective therapies are limited to a small percentage of people due to the narrow treatment time window and secondary injuries of haemorrhage transformation. 3 Therefore, novel effective therapeutic targets and drugs are urgent to be discovered for ischaemic stroke in addition to thrombolytic treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 45 publications
(64 reference statements)
0
13
0
Order By: Relevance
“…The neurological score measured by the mNSS test was performed before GBCA injections and found no significant difference among all groups ( p = 0.659) and either gadobutrol or gadopentetate failed to alter mNSS scores on day 1 p. i (p = 0.845) (Figure 3B). With TTC staining, the infarct area remained unstained (white) and non‐infarct area was stained red 25 . As shown in Figure 3C,D, there was no significant difference in infarct volume among all groups ( p = 0.961).…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…The neurological score measured by the mNSS test was performed before GBCA injections and found no significant difference among all groups ( p = 0.659) and either gadobutrol or gadopentetate failed to alter mNSS scores on day 1 p. i (p = 0.845) (Figure 3B). With TTC staining, the infarct area remained unstained (white) and non‐infarct area was stained red 25 . As shown in Figure 3C,D, there was no significant difference in infarct volume among all groups ( p = 0.961).…”
Section: Resultsmentioning
confidence: 87%
“…Scale bar = 100 μm stained red. 25 As shown in Figure 3C,D, there was no significant difference in infarct volume among all groups (p = 0.961). Meanwhile, Nissl staining showed consistent results (Figure 3E).…”
Section: 2mentioning
confidence: 76%
See 1 more Smart Citation
“…Oridonin could prevent NLRP3 inflammasome complex assembly against NLRP3 inflammasome activation (He et al, 2018). The study found oridonin prevented oxidative stress-induced endothelial injury via promoting the Nrf2 pathway and thereby repaired BBB integrity, alleviated neuroinflammation, and infarct volume after ischemic stroke (Li et al, 2021a).…”
Section: Novel Inhibitormentioning
confidence: 86%
“…The chemical structure of oridonin was first characterized by Fujita et al (Figure 1B). 25 In the following decades, accumulating evidence has indicated that oridonin exhibits multiple biological effects, including anticancer, 26 anti‐inflammatory, 23 antibacterial, 27 antioxidative, 28 antifibrotic, 29 and cytoprotective effects 30 in different disease models. Oridonin consists of four parts, including A, B, C, and D rings; furthermore, it also contains several hydroxyls, one ether, and one α, β‐unsaturated ketone that can form covalent bonds with cysteine residues.…”
Section: Oridonin and Its Derivative Compoundsmentioning
confidence: 99%